Interakce při řešení problémově orientovaných úloh ve výuce přírodovědy - Tereza Češková (Karolinum Press, 2020)
It has been over ten years since the key competences were introduced into the Czech curricula; however, there are still lots of teachers who do not fully understand how to implement these competences in their teaching and instruction. This paper focuses on one of them: the problem-solving competence. In our previous research, we found that a well-designed assignment of a problem-oriented task does not guarantee developing of problem-solving competence. From our research, a need to focus on the execution of the problem-oriented task as such has emerged. The presented study aims to describe the interaction between the teacher and pupils while solving the problem-oriented situation developed around the problem-oriented task. I used the method of a conversation analysis of 15 problem-oriented situations selected from 10 primary science lessons, collected in 2010/2011 in five classes (in two subsequent lessons). My analysis shows that interactions in problem-oriented instruction have overall looser character of institutional rules; the teachers´ role is rather inhibited as they let the pupils come up with their solutions more independently, intervening in the process only if necessary - e.g. to narrow down the problem space or to help by bringing an analogy from a different context. However, the teachers never provide explicit prompts leading to direct solution of the task nor reveal the correct solution. There are also differences in the way they provide feedback and rapport during the problem-oriented situations. For instance, when the teachers ask for an explanation or justification, they elicit a specification or providing other possible solutions instead of correcting the students. In conclusion, I discuss the connection between the explored interactions and scaffolding, limitations of my research and the potentials of follow-up research to understand in more depth how to support the development of pupils problem-solving competence.